Reflections about mental health policies in Brazil from of historical and legislative landmarks (Research, Society and Development, 2024)
Aim: to present reflections about Brazilian mental health policies considering a timeline with the main historical and legislative landmarks related to these policies. Method: This is a critical reflection toward Brazilian mental health policies based on historical and legislative landmarks that represent the administrative organization. Such reflection was based in legal norms, regulations, ordinances and resolutions of Brazilian legislation, scientific productions and information reported by the journalistic media. Results: A timeline of the main mental health legislation in Brazil was presented, in which the main events and characters that contributed to the development of such policies were presented, as well as the discussion on advances and challenges related to mental health policies. Conclusions: This material can contribute to the training of professionals and to instigate reflections, discussions and actions that promote social participation in the formulation of public policies in defense of the right to mental health, citizenship and human dignity.